2021
DOI: 10.1016/j.jsams.2021.02.008
|View full text |Cite
|
Sign up to set email alerts
|

The value of MRI STIR signal intensity on return to play prognosis and reinjury risk estimation in athletes with acute hamstring injuries

Abstract: Objectives: Previous studies have shown low to moderate evidence for a variety of magnetic resonance imaging (MRI) features as prognostic factors in athletes with hamstring injuries. Short-tau inversion recovery (STIR) signal intensity has not yet been investigated for assessing the prognosis of acute muscle injuries. Our aim was to explore the relationship between MRI STIR signal intensity and time to return to play (RTP) and to investigate the association between MRI STIR and reinjury risk in athletes with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…9 Furthermore, recent work showed that edema is often still present upon RTP and is therefore not an appropriate outcome measure to indicate recovery or to predict the recovery time. 12 Therefore, there is a clinical need to explore advanced, quantitative methods to characterize muscle tissue recovery after severe injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Furthermore, recent work showed that edema is often still present upon RTP and is therefore not an appropriate outcome measure to indicate recovery or to predict the recovery time. 12 Therefore, there is a clinical need to explore advanced, quantitative methods to characterize muscle tissue recovery after severe injury.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, Reurink and colleagues showed that only the absence of hyperintense signal on fluid‐sensitive sequences was moderately associated with a shorter time to return to play (RTP) and that proximal tendon involvement was associated with a longer time to RTP 9 . Furthermore, recent work showed that edema is often still present upon RTP and is therefore not an appropriate outcome measure to indicate recovery or to predict the recovery time 12 . Therefore, there is a clinical need to explore advanced, quantitative methods to characterize muscle tissue recovery after severe injury.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that in recent years certain publications have downplayed or questioned the role of MRI in monitoring muscle injuries [ 21 , 26 ], the current results demonstrate that certain MRI findings are predictive of reinjuries and may be a useful tool in the multifactorial decision-making process of recovery and RTP [ 35 37 ].…”
Section: Discussionmentioning
confidence: 83%
“…Also, global improvement in oedema was frequently observed in non-reinjury and reinjury groups in similar percentage. In other studies, different patterns of muscle interstitial oedema in both baseline and control MRI prior to RTP have not been assessed, with previous results primarily based on the measurable extent of oedema [ 20 , 23 , 26 ]. The cotton-like oedema that we have shown in our study is similar to the peritendinous ovoid or subfascial ring oedema indicated by Kho et al [ 34 ] in professional soccer players with suspected acute thigh muscle injuries, that they called exercise-related signal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation